1997
DOI: 10.1074/jbc.272.6.3330
|View full text |Cite
|
Sign up to set email alerts
|

Cripto Enhances the Tyrosine Phosphorylation of Shc and Activates Mitogen-activated Protein Kinase (MAPK) in Mammary Epithelial Cells

Abstract: Cripto-1 (CR-1), a recently discovered protein of the epidermal growth factor (EGF) family, was found to interact with a high affinity, saturable binding site(s) on HC-11 mouse mammary epithelial cells and on several different human breast cancer cell lines. This receptor exhibits specificity for CR-1, since other EGF-related peptides including EGF, transforming growth factor ␣, heparin-binding EGF-like growth factor, amphiregulin, epiregulin, betacellulin, or heregulin ␤1 that bind to either the EGF receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 35 publications
3
84
0
1
Order By: Relevance
“…Two separate assays, mammosphere formation and milk protein expression, showed that overexpression of Cr-1 led to decreased differentiation. In agreement with our data, a 47-mer, containing the EGF-like motif only of recombinant human CR-1 is able to stimulate proliferation and inhibit b-casein expression in mouse HC11 mammary epithelial cells (Kannan et al, 1997). It is generally accepted that proliferation rates are inversely related to differentiation, and we demonstrated here that Cr-1 stimulated the proliferation needed to bring the cells to the state required (equivalent to pregnancy) for differentiation (lactation) but inhibited the differentiation process itself.…”
Section: Discussionsupporting
confidence: 80%
“…Two separate assays, mammosphere formation and milk protein expression, showed that overexpression of Cr-1 led to decreased differentiation. In agreement with our data, a 47-mer, containing the EGF-like motif only of recombinant human CR-1 is able to stimulate proliferation and inhibit b-casein expression in mouse HC11 mammary epithelial cells (Kannan et al, 1997). It is generally accepted that proliferation rates are inversely related to differentiation, and we demonstrated here that Cr-1 stimulated the proliferation needed to bring the cells to the state required (equivalent to pregnancy) for differentiation (lactation) but inhibited the differentiation process itself.…”
Section: Discussionsupporting
confidence: 80%
“…Our lab has previously demonstrated that CR-1 can activate the ras/raf/MAPK and PI3-K/AKT/GSK-3b signaling pathways Kannan et al, 1997;Ebert et al, 1999;Bianco et al, 2004). Interestingly, activation of these signaling pathways can be achieved with a soluble GPI-truncated CR-1 recombinant protein Bianco et al, 2002b).…”
Section: Glypican-1/c-src/mapk/akt Signaling Pathwaymentioning
confidence: 99%
“…17 ± 20 With respect to intracellular signaling, CR-1 is able to activate the ras/raf/ MEK/MAPK and the PI3-kinase signaling pathways. 9,11,13 In this regard, the activation of p21 ras and PI3-kinase has been linked to the ability of CR-1 to inhibit the expression of b-casein and WAP in mouse mammary HC11 epithelial cells and in primary cultures of midpregnant mouse mammary epithelial cells. 9 The present study was designed to ascertain if CR-1 might modulate apoptosis in HC-11 mouse mammary epithelial cells under conditions where b-casein expression is inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike other EGF-like proteins, the human CR-1 protein lacks a conventional hydrophobic signal peptide and transmembrane domain and the modified EGF-like motif which is also possessed by other members of the EGF-CFC family, lacks the A loop, while the B loop is truncated. 13 Another feature that distinguishes CR-1 from other EGF-like peptides is the failure of CR-1 to directly bind to any of the known c-erb-B type 1 receptor tyrosine kinases. 13 However, CR-1 can indirectly induce a transient increase in the tyrosine transphosphorylation of cerb-B 4 in mouse and human mammary epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation